Design of IGBT Drive Circuit for the Motor Controller of Electric Vehicle Based on ACPL-32JT - XIA Yifan; WANG Zhengyu; CHEN Jianming; YANG Hongbo; ZHANG Xinlin (Kongzhi Yu Xinxi Jishu)
It introduced an automotive gate drive optical coupler ACPL-32JT, analyzed the structure and working principle of its typical application circuit and designed an IGBT gate drive circuit with compact circuit structure which based on the optical coupler. Experimental results show that this drive circuit can greatly match IGBT and meets the design requirements.